Performance Test of Hammer Mill and Burr Mill For Soybean - S., Sumardi H.; Komar, Nur; Indrastuti, Y. E. (Jurnal Teknologi Pertanian, 2002)
The objectives of this research are 1) to find out the proper moisture content and angular velocity of Hammer mill and Burr mill for milling, 2) to select the proper milling machine for certain material and 3) to find out the optimum milling yield. Performance test to both type of soy bean milling machine shows that the greater the angular velocity the more the capacity, the lesser the  fineness modulus and the greater the theoretical energy requirement.  The result of the effect of moisture content ranged at 12% to 20% to performance of both type of milling machine indicate that greater moisture content result in reduced capacity, increased fineness modulus and reduced theoretical energy requirement. Hammer mill gives optimum yield at 4000 rpm of angular velocity and 12% moisture content which are 3.94 kg/h of milling capacity, 2.26 of fineness modulus and 24.16 W of theoretical energy requirement.  Burr mill gives optimum yield at 1200 rpm of angular velocity and 12% moisture content which are 3.40 kg/h of milling capacity, 2.10 of fineness modulus and 26.48 W of theoretical energy requirement.   Key words: milling machine, Burr mill, Hammer mill, rpm,  soybean, moisture content